Unsur Elemen tak Tereduksi (Irreducible Element) Realisme Magis Dalam Novel Bumi Karya Tere Liye - Ananda Farah Salsabila; Karkono Karkono (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Magical realism is a theory by Wendy B. Faris that tells about a narrative that combines the elements of fantasy and reality. The term magical realism was created in 1925 throughout the world of painting and was introduced by Franz Roh, a German art critic. The novel Bumi by Tere Liye that was published in 2014 has the concept of magical realism in it. The writing in this novel contains an imaginary adventure where the main characters are trying to find their true self until they reach the parallel universe. This qualitative research uses a library research method. The data collected were verbal and linguistic data that contains an irreducible element in the data source that is the novel Bumi by Tere Liye. Irreducible element contained in the narrative includes the magical abilities of the main characters, such as Raib who can turn invisible, Seli who can radiate blue lightning, and Ali who can transform into a giant bear. There are also magical objects in this novel, such as the moving alley, The Book of Life, The Sun gloves, and others. The existence of a parallel universe is also a factor that strengthens the irreducible element in this novel. Keywords: magical realism, irreducible element, Bumi novel Abstrak: Realisme magis adalah sebuah teori yang dirumuskan oleh Wendy B. Faris mengenai narasi yang memadukan unsur fantasi dan realita. Istilah realisme magis lahir pada 1925 melalui dunia lukis dan diperkenalkan oleh Franz Roh, seorang kritikus seni Jerman. Novel Bumi karya Tere Liye yang terbit pada tahun 2014 mengangkat konsep realisme magis. Penulisan dalam novel ini mengandung petualangan imajinasi dimana para tokoh-tokoh utamanya dikisahkan bahwa mereka sedang berada dalam petualangan mencari jati diri mereka dan pencarian itu mereka lakukan hingga ke dunia paralel. Penelitian kualitatif ini menggunakan pendekatan kepustakaan. Data yang dikumpulkan berupa data verbal dan kebahasaan yang mengandung unsur Irreducible Element dalam sumber data berupa novel Bumi karya Tere Liye. Unsur Irreducible Element yang terdapat dalam narasi meliputi kemampuan magis tokoh-tokoh utama, seperti Raib yang dapat berubah menjadi tak kasat mata, Seli yang dapat memancarkan petir biru, dan Ali yang dapat berubah menjadi beruang raksasa. Dalam novel ini juga terdapat objek-objek magis seperti lorong berpindah, Buku Kehidupan, sarung tangan Klan Matahari, dan lain sebagainya. Keberadaan Dunia Paralel juga merupakan faktor yang memperkuat unsur Irreducible Element dalam novel ini. Kata kunci: realisme magis, irreducible element, novel Bumi